The interplay between credit standards and credit demand: Microeconometric evidence from Denmark - Andreas Kuchler (Danmarks Nationalbank, 2012)
This paper analyses the role of bank-specific and business cycle factors in explaining the development of credit standards and loan volumes of the larger Danish banks during the recent financial crisis. The analysis is based on a unique panel data set combining the individual answers from the Danish Bank Lending Survey with bank characteristics such as loan volumes and prices. We find that business cycle variables and the financial soundness of the individual bank are important factors in explaining its credit standards. We also find that credit standards and credit demand play complementary roles for loan developments at the individual bank level. Throughout most of the study period, shocks to credit demand are significantly related to growth in lending. Changes in credit standards have mainly played a role after the collapse of Lehmann Brothers in early 2009, and during the peak of the sovereign debt crisis in late 2011 and early 2012.
Keywords: E30; E32; E51; G21; 330; credit standards; loan growth; bank lending survey; Kreditwürdigkeit; Kreditgeschäft; Dänemark